Effect of Lavender Inhalation Aromatherapy on Sleep Quality in Cancer Patients at Murni Teguh Memorial Hospital - Dewi Mustikani Saragih; Siti Zahara Nasution; Sumaiyah Sumaiyah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Sleep is a physiological human need. Sleep disorders can affect a person's quality of life. One of the complementary therapies is aromatherapy, which can improve one's sleep quality non-pharmacologically. This study aims to identify the effect of lavender inhalation aromatherapy intervention on sleep quality in cancer patients. The research method used is quantitative or quantitative design with a quasi-experimental design non-equivalent approach. The sampling technique is a non-probability sampling technique, namely the convenience sampling method. Respondents to this study were hospitalized cancer patients totaling 100 respondents consisting of 50 respondents for the intervention group and 50 respondents for the control group. Data was collected using a questionnaire. The sleep quality measurement instrument used is the Sleep Quality Questionnaire. Data were analyzed using the dependent t-test and independent t-test. The results of the study found an effect of lavender inhalation aromatherapy on improving sleep quality in cancer patients with a p-value (p=0.000). Conclusion Lavender inhalation aromatherapy can improve sleep quality in cancer patients and is recommended as a nursing intervention and alternative therapy to improve sleep quality in cancer patients. Keyword: Cancer, Lavender Aromatherapy, Sleep quality